INOVASI APLIKASI SAKTI (SISTEM ADMINISTRASI KEPENDUDUKAN BERBASIS TEKNOLOGI INFORMASI) PADA PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KOTA KEDIRI - Rizha Ayu Widoretno, Yasinta; Sunu Astuti, Retno; Zarkasyi Rahman, Amni (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
SAKTI application was implemented by the Kediri City Population and Civil Registration Department as an innovative solution aimed at improving service quality and overcoming various public service problems. However, there are some problems with the application such as software unresponsiveness, frequent errors due to the lack of data integration, and low adoption rates. This research aims to analyze the innovation of the SAKTI application and the factors that encourage and inhibit it. The research was conducted using a qualitative descriptive method, involving data collection techniques through interviews, documentation, and observation. The innovation theory according to Rogers is used to analyze the SAKTI application innovations, which are identified through 1) aspects of innovation characteristics, including relative advantage, compatibility, complexity, trialability, and observability; 2) Communication channel aspects, and 3) Social system aspects. Fontana, Harrington Emerson, and Mulgan&Albury's theory is used to analyze the factors that drive and hinder the innovation of the SAKTI application. The results of this research show that SAKTI application innovation has made it easier, faster, and more affordable, thereby improving the quality of services by the Kediri City Population and Civil Registration Department. However, some people are still unable to use the application due to a lack of access to compatible devices or insufficient technological skills. The driving factors of innovation are driven by organizational factors that can provide adequate infrastructure and human resources factors that are competent in providing services. Technological factors becomes the inhibitor of the innovation due to network system errors and the public's lack of understanding of the SAKTI application causes administrative barriers.